An investigation of the possible correlations between kimberlite lithophases and their indicator mineral compositions at Finsch Diamond Mine, Northern Cape Province, South Africa - Thunsi, Karabo (Department of Geological Sciences, 2026)
Kimberlite indicator minerals (KIMs) are distinct mantle-derived minerals such as garnet, clinopyroxene, chromite and ilmenite, which are brought to surface by kimberlite volcanism. Kimberlite indicator minerals are mainly used in assessing the petrogenetic history of kimberlites, however KIMs are also used to infer the diamond potential of kimberlites in exploration programmes. Kimberlite indicator minerals recovered as heavy mineral concentrates show compositional variations in Cr2O3, CaO, MgO, FeO and TiO2 that reflect the chemical, thermal and lithological environments in which they formed, as well as the probability of association with diamond. In this study, the petrogenetic history of the Finsch kimberlite is derived and mineral compositional attributes of heavy mineral concentrates are identified and, correlations (or lack thereof) are noted with the occurrence of diamonds, in association with a revised descriptive geological nomenclature of the Finsch kimberlite. This is achieved through the major and trace element analysis of KIMs separated as heavy mineral concentrates from kimberlite samples using a simplified characterization technique for KIMs. The results of this investigation suggest that the Finsch kimberlite is characterized by lithophase units with three textural types: pyroclastic (unit F1), hypabyssal (units F2 and F4) and transitional (units F2, F3, F5/F6 and F8), with the occurrence of melt segregationary textures in units F1, F2, F3, F5/F6 and F8, indicating emplacement of a volatile-rich magma that effectively transported and retained mantle xenocrystic material during emplacement. The petrological characteristics of the different Finsch kimberlite units are mainly attributed to the emplacement style and melt interaction of each unit. Garnet and clinopyroxene recovered from the various Finsch kimberlite units are particularly useful in associating the occurrence of KIM, to diamondiferous mantle rocks. The lithophase units of the Finsch kimberlite (except for unit F3, which contains very few garnets) are characterized by dominantly peridotitic garnets, with similar compositional ranges in terms of major element and trace element compositions (e.g., with typically low Zr and Y contents and sinusoidal to positively sloped REE patterns, with individual REE contents typically less than 10x chondrites). The diamond potential of the Finsch kimberlite is demonstrated through the occurrence of a significant proportion of the garnets falling in the G10 field as well as eclogitic garnets typically showing characteristics of Group 1 and diamondiferous eclogites. Clinopyroxene is mainly characterized by low Al₂O₃ contents and moderate Cr₂O₃ contents, that overlap in terms of Mg#, Ca# and Na content with lherzolitic clinopyroxene from granular lherzolites from Finsch and other kimberlites on the Kaapvaal craton. Single mineral thermobarometry for garnet and clinopyroxene yields a similar range of temperature and pressure values (800 – 1200°C vs. 850 – 1300°C and 2.2 – 5.5 vs. 2.2 – 6.5 for garnet and clinopyroxene, respectively). The petrological, geochemical vi and thermobarometric results from this study demonstrate that the Finsch kimberlite was emplaced by moderately to strongly pyroclastic eruptive processes that were effective in sampling and conveying mantle xenolithic material (and diamonds) to the near surface. Further, it sampled a lithologically heterogeneous, but dominantly peridotitic lithospheric mantle with minor eclogitic components. A significant proportion of the sampled KIM have compositions associated with diamonds (e.g., such as G10 garnets or with compositions overlapping with Finsch diamond inclusions) and pressure and temperature values lying within the diamond stability field. However, the majority of KIMs appear to be derived from lherzolitic lithologies and, likely originated from pressures too low to lie in the diamond stability field. Little overall correlation between kimberlite textural type and KIM populations and parageneses is apparent.